Lessons from GPS-tagged Eurasian Curlews: synthesising movement ecology to inform conservation - Frédéric Jiguet; Aurélien Besnard; Pierrick Bocher; Andrea Kölzsch; Aleksi Lehikoinen; Markus Piha; Petr Procházka; Marie Donnez; Tuomas Seimola; Jimmy Allain; Lise Bartholus; Carole Doucerain; et al. (Biological Conservation, 2026)

Balancing biodiversity and economics: Using robust Pareto-optimisation to quantify ecological–economic trade-offs in German mixed beech forests - Julia Klenke; Volker von Groß; Jasper M. Fuchs; Larissa R. Topanotti; Benjamin Wildermuth; Carmen Alicia Rivera Pérez; Jing-Zhong Lu; Likulunga Emmanuel Likulunga; Thomas Knoke; Carola Paul (Ambio, 2026)
Biodiversity loss threatens forest ecosystem stability and functioning, while measures to enhance biodiversity trade-off with economic performance. Native tree-species mixtures are promoted to support associated taxa but usually underperform economically compared to non-native species, both in pure and admixed stands. Quantifying ecological–economic trade-offs remains challenging due to uncertainties in economic and biodiversity indicators. Using empirical data on economic (land rent/annuity) and biodiversity indicators (species richness) of five forest taxa from Central German forests, we applied multicriteria optimisation to forest stand-type compositions. We assess the compositional shift of pure (beech, spruce, Douglas-fir) and mixed stand types (beech–spruce, beech–Douglas-fir) under increasing biodiversity targets, accounting for uncertain indicator provision. Stand-type portfolios became more diversified with increasing biodiversity targets. Biodiversity-economic trade-offs were efficiently reduced by incorporating Douglas-fir (in pure and mixed stands) into the portfolio. However, enhancing biodiversity created economic loss, underscoring the need for financial compensation schemes.

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

Quantifying the influence of avalanche release volume on runout probability: A case study of a mountain road section - Stefan Oberndorfer; Jan-Thomas Fischer; Sven Fuchs (Cold Regions Science and Technology, 2026)

Covalent organic frameworks (COFs) functionalized with boronate and triazole moieties for selective adsorption of d-fructose - Tobias Riedl; Pia Groß; Leonie Sophie Häser; Runa Tschekorsky Orloff; Theresa Röper; Thomas Fuchs; Stephanie Bachmann; Ann-Christin Pöppler; Herwig Peterlik; Andreas Jupke; Regina Palkovits; Irina Delidovich (Chemical Engineering Journal, 2025)

Multi-method luminescence dating of late Cenozoic northern Upper Rhine Graben fluvial sediments - Anna-Lena Geis; Mariana Sontag-González; Thomas Kolb; Mayank Jain; Markus Fuchs (Quaternary Geochronology, 2025)

Leaky pollination barrier in edaphic vicarious alpine plants - Thomas Huber; Roman Fuchs; Julian Robin; Andreas Tribsch; Stefan Dötterl; Hanno Schaefer (Arthropod-Plant Interactions, 2025)
Adaptation to siliceous versus carbonate substrates is thought to be an important driver of speciation in the alpine flora. The role of the pollination system in the formation and maintenance of such species is presently unclear. Here, we chose three species pairs in the genera Gentiana , Primula , and Rhododendron which often occur in geographic proximity or even sympatry to study the existence of pollination barriers in these lineages. Using remote camera and direct observation approaches, scent and color analyses, we tested the hypothesis whether divergent pollinator communities exist that could help to maintain genetic separation of plant populations adapted to different soil types. We found differences in frequency, diurnal activity and to some extent also community composition of flower visitors in edaphic vicarious species pairs. Floral traits like color and scent as well as flower visitor co-distributions indicate that our study species have divergent but overlapping pollination systems. Our results do not suggest a strong reproductive barrier function of the pollination system. While adaptation to different soils still seems to be the main force keeping edaphic vicarious alpine plants genetically separated, pollinators might mediate hybridization in contact areas.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

The Pannonian-Carpathian-Alpine seismic experiment (PACASE): network description and implementation - Antje Schlömer; György Hetényi; Jaroslava Plomerová; Luděk Vecsey; Miroslav Bielik; Götz Bokelmann; Kristian Csicsay; Wojciech Czuba; Lucia Fojtíková; Wolfgang Friederich; Florian Fuchs; Marek Grad; et al. (Acta Geodaetica et Geophysica, 2024)
The Pannonian-Carpathian-Alpine Seismic Experiment (PACASE) is a collaborative project based on a large, passive seismic network comprising 214 temporary stations. Among the primary aims are the imaging of the Earth’s crustal, lithospheric and upper mantle structure, including joint inversions; monitoring and mapping of seismic activity; and interpretation of the data from seismotectonic and geodynamic perspectives. The base of the cooperation is a high-quality, broadband seismic network covering the very centre of Europe: the Eastern Alpine and Western Carpathian Mountain ranges, the Bohemian Massif, and the sedimentary Molasse and Pannonian Basins. In this overview, we focus on the implementation and achieved field goals of PACASE, such as seismic station configuration, general network organization, data availability and access to the dataset. With selected seismological examples, we demonstrate the good usability of the records of earthquake detection, and a first publication attests to the structural imaging capability of the PACASE data. We assess the background noise level at various stations and its variations in time and space. Our aim is to collect all practical information relevant to serve as a long-term reference for the PACASE.

Investigation on the thermal budget and flow field of a manikin and comparison with human subject in different scenarios - Abhilash Sankaran; Rainer Hain; Christina Matheis; Thomas Fuchs; Victor Norrefeldt; Gunnar Grün; Christian J. Kähler (Building and Environment, 2024)

Archaeopedological reconstruction of Middle Bronze Age subsistence farming in SW-Germany from sedimentary archives in the Western Allgäu - Sascha Scherer; Benjamin Höpfer; Katleen Deckers; Markus Fuchs; Ellen Kandeler; Eva Lehndorff; Johanna Lomax; Sven Marhan; Christian Poll; Wroth Kristen; Thomas Knopf; Thomas Scholten; et al. (Geoderma Regional, 2023)

Improving an existing proxy-based approach for floodplain denitrification assessment to facilitate decision making on restoration - Ute Susanne Kaden; Christiane Schulz-Zunkel; Elmar Fuchs; Peter Horchler; Hans Dieter Kasperidus; Otavio de Moraes Bonilha; Holger Rupp; Martin Tschikof; Gabriele Weigelhofer; Thomas Hein; Mathias Scholz (Science of The Total Environment, 2023)

The subsurface thermal state of Svalbard and implications for geothermal potential - Kim Senger; Matthijs Nuus; Niels Balling; Peter Betlem; Tom Birchall; Hanne H. Christiansen; Harald Elvebakk; Sven Fuchs; Malte Jochmann; Peter Klitzke; Kirsti Midttømme; Snorre Olaussen; et al. (Geothermics, 2023)

Pentalinonsterol, a Phytosterol from Pentalinon andrieuxii, is Immunomodulatory through Phospholipase A2 in Macrophages toward its Antileishmanial Action - Sanjay Varikuti; Andrew B. Shelton; Sainath R. Kotha; Travis Gurney; Gaurav Gupta; Thomas J. Hund; James R. Fuchs; A. Douglas Kinghorn; Nidhi Srivastava; Abhay R. Satoskar; Narasimham L. Parinandi (Cell Biochemistry and Biophysics, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Endothelin receptors in renal interstitial cells do not contribute to the development of fibrosis during experimental kidney disease - Thomas H. Neder; Julia Schrankl; Michaela A. A. Fuchs; Katharina A. E. Broeker; Charlotte Wagner (Pflügers Archiv - European Journal of Physiology, 2021)
Renal interstitial fibrosis is characterized by the development of myofibroblasts, originating from resident renal and immigrating cells. Myofibroblast formation and extracellular matrix production during kidney damage are triggered by various factors. Among these, endothelins have been discussed as potential modulators of renal fibrosis. Utilizing mouse models of adenine nephropathy (AN) and unilateral ureter occlusion (UUO), this study aimed to investigate the contribution of endothelin signaling in stromal mesenchymal resident renal interstitial cells. We found in controls that adenine feeding and UUO caused marked upregulations of endothelin-1 (ET-1) gene expression in endothelial and in tubular cells and a strong upregulation of ET A -receptor (ET A -R) gene expression in interstitial and mesangial cells, while the gene expression of ET B -receptor (ET B -R) did not change. Conditional deletion of ET A -R and ET B -R gene expression in the FoxD1 stromal cell compartment which includes interstitial cells significantly reduced renal ET A -R gene expression and moderately lowered renal ET B -R gene expression. ET receptor (ET-R) deletion exerted no apparent effects on kidney development nor on kidney function. Adenine feeding and UUO led to similar increases in profibrotic and proinflammatory gene expression in control as well as in ET A flfl ET B flfl FoxD1 Cre+ mice (ET-Ko). In summary, our findings suggest that adenine feeding and UUO activate endothelin signaling in interstitial cells which is due to upregulated ET A -R expression and enhanced renal ET-1 production Our data also suggest that the activation of endothelin signaling in interstitial cells has less impact for the development of experimentally induced fibrosis.

A comprehensive phenotypic characterization of a whole-body Wdr45 knock-out mouse - Caroline A. Biagosch; Silvia Vidali; Michael Faerberboeck; Svenja-Viola Hensler; Lore Becker; Oana V. Amarie; Antonio Aguilar-Pimentel; Lillian Garrett; Tanja Klein-Rodewald; Birgit Rathkolb; Enrica Zanuttigh; Julia Calzada-Wack; et al. (Mammalian Genome, 2021)
Pathogenic variants in the WDR45 (OMIM: 300,526) gene on chromosome Xp11 are the genetic cause of a rare neurological disorder characterized by increased iron deposition in the basal ganglia. As WDR45 encodes a beta-propeller scaffold protein with a putative role in autophagy, the disease has been named Beta-Propeller Protein-Associated Neurodegeneration (BPAN). BPAN represents one of the four most common forms of Neurodegeneration with Brain Iron Accumulation (NBIA). In the current study, we generated and characterized a whole-body Wdr45 knock-out (KO) mouse model. The model, developed using TALENs, presents a 20-bp deletion in exon 2 of Wdr45 . Homozygous females and hemizygous males are viable, proving that systemic depletion of Wdr45 does not impair viability and male fertility in mice. The in-depth phenotypic characterization of the mouse model revealed neuropathology signs at four months of age, neurodegeneration progressing with ageing, hearing and visual impairment, specific haematological alterations, but no brain iron accumulation. Biochemically, Wdr45 KO mice presented with decreased complex I (CI) activity in the brain, suggesting that mitochondrial dysfunction accompanies Wdr45 deficiency. Overall, the systemic Wdr45 KO described here complements the two mouse models previously reported in the literature (PMIDs: 26,000,824, 31,204,559) and represents an additional robust model to investigate the pathophysiology of BPAN and to test therapeutic strategies for the disease.

Missense and truncating variants in CHD5 in a dominant neurodevelopmental disorder with intellectual disability, behavioral disturbances, and epilepsy - Ilaria Parenti; Daphné Lehalle; Caroline Nava; Erin Torti; Elsa Leitão; Richard Person; Takeshi Mizuguchi; Naomichi Matsumoto; Mitsuhiro Kato; Kazuyuki Nakamura; Stella A. de Man; Heidi Cope; et al. (Human Genetics, 2021)
Located in the critical 1p36 microdeletion region, the chromodomain helicase DNA-binding protein 5 ( CHD5 ) gene encodes a subunit of the nucleosome remodeling and deacetylation (NuRD) complex required for neuronal development. Pathogenic variants in six of nine chromodomain (CHD) genes cause autosomal dominant neurodevelopmental disorders, while CHD5 -related disorders are still unknown. Thanks to GeneMatcher and international collaborations, we assembled a cohort of 16 unrelated individuals harboring heterozygous CHD5 variants, all identified by exome sequencing. Twelve patients had de novo CHD5 variants, including ten missense and two splice site variants. Three familial cases had nonsense or missense variants segregating with speech delay, learning disabilities, and/or craniosynostosis. One patient carried a frameshift variant of unknown inheritance due to unavailability of the father. The most common clinical features included language deficits (81%), behavioral symptoms (69%), intellectual disability (64%), epilepsy (62%), and motor delay (56%). Epilepsy types were variable, with West syndrome observed in three patients, generalized tonic–clonic seizures in two, and other subtypes observed in one individual each. Our findings suggest that, in line with other CHD-related disorders, heterozygous CHD5 variants are associated with a variable neurodevelopmental syndrome that includes intellectual disability with speech delay, epilepsy, and behavioral problems as main features.

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Tryptophan-kynurenine profile in pediatric autoimmune hepatitis - Simon D. Lytton; Marcin Osiecki; MałgorzataWoźniak; Bożena Cukrowska; Aldona Wierzbicka; Maria Goliszek; Piotr Socha; Wojciech Janczyk; Dilek Dayanakli; Dieter Abendroth; Sabine Kramp; Kai Fechner; et al. (Immunologic Research, 2019)

Regionalökonomische Disparitäten im Spiegel vom Raumtypisierungen - Thomas Wieland; Horst Fuchs (Standort, 2018)

The AlpArray Seismic Network: A Large-Scale European Experiment to Image the Alpine Orogen - György Hetényi; Irene Molinari; John Clinton; Götz Bokelmann; István Bondár; Wayne C. Crawford; Jean-Xavier Dessa; Cécile Doubre; Wolfgang Friederich; Florian Fuchs; Domenico Giardini; Zoltán Gráczer; et al. (Surveys in Geophysics, 2018)

Fgf9 Y162C Mutation Alters Information Processing and Social Memory in Mice - Lillian Garrett; Lore Becker; Jan Rozman; Oliver Puk; Tobias Stoeger; Ali Önder Yildirim; Alexander Bohla; Oliver Eickelberg; Wolfgang Hans; Cornelia Prehn; Jerzy Adamski; Thomas Klopstock; et al. (Molecular Neurobiology, 2018)

Correction to: Allocation of risk and benefits—distributional justices in mountain hazard management - Thomas Thaler; Andreas Zischg; Margreth Keiler; Sven Fuchs (Regional Environmental Change, 2018)

Social justice in the context of adaptation to climate change—reflecting on different policy approaches to distribute and allocate flood risk management - Thomas Thaler; Sven Fuchs; Sally Priest; Neelke Doorn (Regional Environmental Change, 2018)

Allocation of risk and benefits—distributional justices in mountain hazard management - Thomas Thaler; Andreas Zischg; Margreth Keiler; Sven Fuchs (Regional Environmental Change, 2018)

Serum Response Factor (SRF) Ablation Interferes with Acute Stress-Associated Immediate and Long-Term Coping Mechanisms - Annemarie Zimprich; Gabi Mroz; Christopher Meyer zu Reckendorf; Sofia Anastasiadou; Philip Förstner; Lillian Garrett; Sabine M. Hölter; Lore Becker; Jan Rozman; Cornelia Prehn; Birgit Rathkolb; Kristin Moreth; et al. (Molecular Neurobiology, 2017)

Persistence with VKA treatment in newly treated atrial fibrillation patients: an analysis based on a large sample of 38,076 German patients - Thomas Wilke; Antje Groth; Andreas Fuchs; Matthias Pfannkuche; Ulf Maywald (European Journal of Clinical Pharmacology, 2017)

Herstellung von polyzyklischen Diterpenen - Ronja Janke; Monika Fuchs; Mathias Christmann; Thomas Brück; Bernhard Loll (BIOspektrum, 2017)

Viable Ednra Y129F mice feature human mandibulofacial dysostosis with alopecia (MFDA) syndrome due to the homologue mutation - Sibylle Sabrautzki; Michael A. Sandholzer; Bettina Lorenz-Depiereux; Robert Brommage; Gerhard Przemeck; Ingrid L. Vargas Panesso; Alexandra Vernaleken; Lillian Garrett; Katharina Baron; Ali O. Yildirim; Jan Rozman; Birgit Rathkolb; et al. (Mammalian Genome, 2016)

Micro-sized enterprises: vulnerability to flash floods - Konstantinos Karagiorgos; Micha Heiser; Thomas Thaler; Johannes Hübl; Sven Fuchs (Natural Hazards, 2016)

Foreword: Vulnerability assessment in natural hazard risk—a dynamic perspective - Sven Fuchs; Thomas Glade (Natural Hazards, 2016)

Multi-vulnerability analysis for flash flood risk management - Konstantinos Karagiorgos; Thomas Thaler; Johannes Hübl; Fotios Maris; Sven Fuchs (Natural Hazards, 2016)

Exome sequencing identifies a nonsense mutation in Fam46a associated with bone abnormalities in a new mouse model for skeletal dysplasia - Susanne Diener; Sieglinde Bayer; Sibylle Sabrautzki; Thomas Wieland; Birgit Mentrup; Gerhard K. H. Przemeck; Birgit Rathkolb; Elisabeth Graf; Wolfgang Hans; Helmut Fuchs; Marion Horsch; Thomas Schwarzmayr; et al. (Mammalian Genome, 2016)

Evolving inter-regional co-operation in flood risk management: distances and types of partnership approaches in Austria - Thomas A. Thaler; Sally J. Priest; Sven Fuchs (Regional Environmental Change, 2016)

Enhancement of functional connectivity, working memory and inhibitory control on multi-modal brain MR imaging with Rifaximin in Cirrhosis: Implications for the gut-liver-brain axis - Vishwadeep Ahluwalia; James B. Wade; Douglas M. Heuman; Thomas A. Hammeke; Arun J. Sanyal; Richard K. Sterling; R. Todd Stravitz; Velimir Luketic; Mohammad S. Siddiqui; Puneet Puri; Michael Fuchs; Micheal J. Lennon; et al. (Metabolic Brain Disease, 2014)

Identification of structural proteins of koi herpesvirus - Walter Fuchs; Harald Granzow; Malte Dauber; Dieter Fichtner; Thomas C. Mettenleiter (Archives of Virology, 2014)

Approach to Cerebrospinal Fluid (CSF) Biomarker Discovery and Evaluation in HIV Infection - Richard W. Price; Julia Peterson; Dietmar Fuchs; Thomas E. Angel; Henrik Zetterberg; Lars Hagberg; Serena Spudich; Richard D. Smith; Jon M. Jacobs; Joseph N. Brown; Magnus Gisslen (Journal of Neuroimmune Pharmacology, 2013)

Development and characterization of attenuated metabolic mutants of Bordetella bronchiseptica for applications in vaccinology - Tetyana Yevsa; Thomas Ebensen; Barbara Fuchs; Beata Zygmunt; Rimma Libanova; Roy Gross; Kai Schulze; Carlos A. Guzmán (Environmental Microbiology, 2013)
Summary Bordetella bronchiseptica is an important pathogen causing a number of veterinary respiratory syndromes in agriculturally important and food‐producing confinement‐reared animals, resulting in great economic losses annually amounting to billions of euros worldwide. Currently available live vaccines are incompletely satisfactory in terms of efficacy and safety. An efficient vaccine for livestock animals would allow reducing the application of antibiotics, thereby preventing the massive release of pharmaceuticals into the environment. Here, we describe two new potential vaccine strains based on the BB7865 strain. Two independent attenuating mutations were incorporated by homologous recombination in order to make negligible the risk of recombination and subsequent reversion to the virulent phenotype. The mutations are critical for bacterial metabolism, resistance to oxidative stress, intracellular survival and in vivo persistence. The resulting double mutants BB7865 risA aroA and BB7865 risA dapE were characterized as promising vaccine candidates, which are able to confer protection against colonization of the lower respiratory tract after sublethal challenge with the wild‐type strain.

Vulnerability assessment in natural hazard and risk analysis: current approaches and future challenges - Sven Fuchs; Jörn Birkmann; Thomas Glade (Natural Hazards, 2012)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

How to uncoil your partner—“mating songs” in giant pill-millipedes (Diplopoda: Sphaerotheriida) - Thomas Wesener; Jörn Köhler; Stefan Fuchs; Didier van den Spiegel (The Science of Nature, 2011)

GOCE gravitational gradients along the orbit - Johannes Bouman; Sophie Fiorot; Martin Fuchs; Thomas Gruber; Ernst Schrama; Christian Tscherning; Martin Veicherts; Pieter Visser (Journal of Geodesy, 2011)

Generation and characterization of koi herpesvirus recombinants lacking viral enzymes of nucleotide metabolism - Walter Fuchs; Dieter Fichtner; Sven M. Bergmann; Thomas C. Mettenleiter (Archives of Virology, 2011)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Variable DNA content of Cyclamen persicum regenerated via somatic embryogenesis: rethinking the concept of long-term callus and suspension cultures - Thomas Borchert; Jörg Fuchs; Traud Winkelmann; Annette Hohe (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Morphologic and molecular characterization of two novel Krt71 (Krt2-6g) mutations: Krt71 rco12 and Krt71 rco13 - Fabian Runkel; Matthias Klaften; Kerstin Koch; Volker Böhnert; Heinrich Büssow; Helmut Fuchs; Thomas Franz; Martin Hrabé de Angelis (Mammalian Genome, 2006)

New ENU-induced semidominant mutation, Ali18, causes inflammatory arthritis, dermatitis, and osteoporosis in the mouse - Koichiro Abe; Helmut Fuchs; Thomas Lisse; Wolfgang Hans; Martin Hrabé de Angelis (Mammalian Genome, 2006)

Examining SLV-323, a novel NK1 receptor antagonist, in a chronic psychosocial stress model for depression - Boldizsár Czéh; Olga Pudovkina; Marieke G. C. van der Hart; Mária Simon; Urs Heilbronner; Thomas Michaelis; Takashi Watanabe; Jens Frahm; Eberhard Fuchs (Psychopharmacology, 2005)

Catecholates and mixed catecholate hydroxamates as artificial siderophores for mycobacteria - Steffen Wittmann; Lothar Heinisch; Ina Scherlitz-Hofmann; Thomas Stoiber; Dorothe Ankel-Fuchs; Ute Möllmann (BioMetals, 2004)

A 500-kb region on chromosome 16p13.1 contains the pseudoxanthoma elasticum locus: high-resolution mapping and genomic structure - Li Cai; Berthold Struk; Mark D. Adams; Wan Ji; Thomas Haaf; Hyung-Lyun Kang; So Hee Dho; Xuequn Xu; Franziska Ringpfeil; Julie Nancarrow; Stéphanie Zäch; Lori Schaen; et al. (Journal of Molecular Medicine, 2000)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Purification and properties of benzyl alcohol dehydrogenase from a denitrifying Thauera sp. - Thomas Biegert; Uwe Altenschmidt; Christoph Eckerskorn; Georg Fuchs (Archives of Microbiology, 1995)

Anaerobic oxidation of toluene (analogues) to benzoate (analogues) by whole cells and by cell extracts of a denitrifying Thauera sp. - Thomas Biegert; Georg Fuchs (Archives of Microbiology, 1995)

Purification and properties of benzyl alcohol dehydrogenase from a denitrifying Thauera sp. - Thomas Biegert; U. Altenschmidt; Christoph Eckerskorn; G. Fuchs (Archives of Microbiology, 1995)

Anaerobic oxidation of toluene (analogues) to benzoate (analogues) by whole cells and by cell extracts of a denitrifying Thauera sp. - Thomas Biegert; G. Fuchs (Archives of Microbiology, 1995)